NATURAL ANTIMICROBIALS IN THE PIPELINE AND POSSIBLE SYNERGISM WITH ANTIBIOTICS TO OVERCOME MICROBIAL RESISTANCE - EMTENAN M HANAFI; ENAS N DANIAL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
The unresponsive use of antibiotics led to the appearance of multiple drug-resistant bacteria strains. Studying the mechanism by which bacteria can resist antibiotics, the so called quorum sensing and biofilm formation, enabled the researchers to find bioactive compounds, derived from eukaryotes and prokaryotes. The disrupt of this mechanism is called quorum sensing inhibitors or quorum quenchers. This article provides an overview on the current research done on such bioactive compounds, the possible use of them as antibiotic alternatives, what are the advantage and disadvantages, the source from which it has been extracted, and how it may succeed to overcome bacterial resistance. The recommendation of researchers is to use some of these natural antimicrobial compounds combined to lower doses of antibiotics for treatment, the fastest way to limit the adverse effects of the exploitation of antibiotics and to avoid bacterial resistance.